1996
DOI: 10.1002/bjs.1800831138
|View full text |Cite
|
Sign up to set email alerts
|

Decreased E-cadherin expression is associated with haematogenous recurrence and poor prognosis in patients with squamous cell carcinoma of the oesophagus

Abstract: Reduced expression of E-cadherin is associated with tumour invasiveness and metastasis. To elucidate whether E-cadherin expression correlates with clinical outcome in patients with oesophageal cancer, 62 patients were investigated immunohistochemically using an anti-E-cadherin monoclonal antibody (HECD-1). Eight patients had normal levels of expression in the tumour, 25 had tumours that expressed high levels (50 per cent or more tumour cells staining positive for E-cadherin) and 29 had tumours expressing low l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
45
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(47 citation statements)
references
References 17 publications
1
45
1
Order By: Relevance
“…In various cancerous tissues, a reduced expression of E-cadherin has frequently been observed in cancer progression (Katagiri et al, 1995;Lipponen and Eskelinen, 1995;Yonemura et al, 1995;Tamura et al, 1996;Nakanishi et al, 1997;Umbas et al, 1997;Bankfalvi et al, 1999;Ghadimi et al, 1999;Zheng et al, 1999;Kase et al, 2000;Gofuku et al, 1999). The aim of this study was to verify immunohistochemically the hypothesis that dysadherin, which suppresses the E-cadherin system, might play a significant role in the aggressiveness of colorectal carcinoma.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In various cancerous tissues, a reduced expression of E-cadherin has frequently been observed in cancer progression (Katagiri et al, 1995;Lipponen and Eskelinen, 1995;Yonemura et al, 1995;Tamura et al, 1996;Nakanishi et al, 1997;Umbas et al, 1997;Bankfalvi et al, 1999;Ghadimi et al, 1999;Zheng et al, 1999;Kase et al, 2000;Gofuku et al, 1999). The aim of this study was to verify immunohistochemically the hypothesis that dysadherin, which suppresses the E-cadherin system, might play a significant role in the aggressiveness of colorectal carcinoma.…”
Section: Discussionmentioning
confidence: 96%
“…Several studies have reported that decreased function of E-cadherin is associated with tumour progression in many cancers, and in particular E-cadherin acts as a suppressor of invasive ability (Behrens et al, 1989;Vleminckx et al, 1991;Hirohashi, 2000). Many immunohistochemical studies evaluating E-cadherin expression in tumour tissues have demonstrated that reduced expression of E-cadherin is frequently observed in cancer progression (Katagiri et al, 1995;Lipponen and Eskelinen, 1995;Yonemura et al, 1995;Tamura et al, 1996;Nakanishi et al, 1997;Umbas et al, 1997;Bankfalvi et al, 1999;Ghadimi et al, 1999;Gofuku et al, 1999;Zheng et al, 1999;Kase et al, 2000).…”
mentioning
confidence: 99%
“…Loss of E-cadherin expression is a well-documented condition for invasiveness; [14][15][16][17][18][19][20] however, this result is debatable. 3,4 Our work demonstrated that the loss of E-cadherin itself, without a mesenchymal phenotype, may not be associated with invasive behavior, whereas tumors with a mesenchymal phenotype, regardless of E-cadherin expression, showed aggressive behavior in esophageal squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Among the various adhesion molecules, the expression of E-cadherin has primarily been investigated, and a significant correlation between its expression and a favorable prognosis in cancer patients, including those with ESCC, has been reported (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%